A comparative study of CE‐SDS, SDS‐PAGE, and Simple Western—Precision, repeatability, and apparent molecular mass shifts by glycosylation. Issue 14 (16th May 2021) - Scheller, Christin; Krebs, Finja; Wiesner, Rebecca; Wätzig, Hermann; Oltmann‐Norden, Imke
Abstract: SDS gel electrophoresis is a commonly used approach for monitoring purity and apparent molecular mass (Mr) of proteins, especially in the field of quality control of biopharmaceutical proteins. The technological installation of CE‐SDS as the replacement of the slab gel technique (SDS‐PAGE) is still in progress, leading to a continuous improvement of CE‐SDS instruments. Various CE‐SDS instruments, namely Maurice (CE‐SDS/CE‐SDS PLUS) and Wes by ProteinSimple as well as the microchip gel electrophoresis system LabChip® GXII Touch™ HT by PerkinElmer were tested for precision and repeatability compared to SDS‐PAGE (Bio‐Rad). For assessing these quality control parameters, standard model proteins with minor post‐translational modifications were used. Overall, it can be concluded that the CE‐SDS‐based methods are similar to SDS‐PAGE with respect to these parameters. Quality characteristics of test systems gain more significance by testing proteins that do not behave like model proteins. Therefore, glycosylated proteins were analyzed to comparatively investigate the influence of glycosylation on Mr determination in the different instruments. In some cases, high deviations were found both among the methods and with regard to reference values. This article provides possible explanations for these findings.